Efisiensi Pemangkasan Cabang dan Pemberian Pupuk KCL pada Fase Generatif Terhadap Produksi Tanaman Semangka (Citrullus vulgaris S.) Varietas Baginda F1 - Yono, Sutari; Putri, Santi Diana (UNIVERSITAS LABUHANBATU, 2023)
Watermelon is a horticultural commodity that is highly favored by the people of Indonesia and has quite high economic value because it tastes sweet and has a lot of water content. One of the obstacles in watermelon cultivation is improper cultivation techniques so that production is not optimal. This study aims to determine the efficiency of pruning watermelon plants and applying KCl fertilizer to watermelon production. This study was arranged based on a completely randomized design (CRD) with two treatment factors, namely A (pruning) consisting of A0 (pruning main branches), A1 (pruning primary branches) and A2 (pruning secondary branches), treatment factor B (KCl Fertilizer) consists of B0 (100 g/plant), B1 (150 g/plant) and B2 (200 g/plant). The parameters observed in this study were plant height, number of nodes, first flower appearance, fruit circumference per sample, fruit weight per sample and total soluble solid content. Based on the results of research on the efficiency of pruning branches and applying KCl fertilizer in the generative phase on the production of the watermelon plant (Citrullus vulgaris S.) of the Baginda F1 variety that has been carried out, it can be concluded that pruning primary branches and applying a dose of 200 g/plant of KCl fertilizer gives good results against variables of fruit circumference and fruit weight as well as pruning of primary branches also gave the best results on the total soluble solit (TSS) value of watermelon. This study was analyzed statistically using analysis of variance (ANOVA) followed by the Duncans New Multiple Range Test (DNMRT) at 5% level.Â Keywords: Branch Pruning, KCl Fertilizer, Watermelon